A chattering-free adaptive second-order non-singular fast terminal sliding mode control scheme for a class of nonlinear uncertain systems. (2018) - Zhang, Beibei; Gao, Shouli; Yang, Xiao; Zhao, Dongya; Zhang, Pengbin; Zeng, Yupei
In this paper, an adaptive second-order non-singular fast terminal sliding mode (SONFTSM) control scheme is proposed so as to achieve finite-time stability with chattering-free control inputs for a class of nonlinear uncertain systems. Instead of the traditional control input in primitive sliding mode switching control design, the real control input is the time integration of the designed derivation of control input with discontinuous terms such that the chattering phenomenon can be reduced. An integral terminal sliding mode (ITSM) and a non-singular fast terminal sliding mode (NFTSM) are applied into the equivalent control design such that finite-time convergence of system states can be guaranteed when it moves on a sliding surface. Then, an adaptive method is utilised to estimate the unknown upper bound of the lumped uncertainty caused by modelling error and external disturbance. The stability analysis of closed-loop system can be demonstrated by constructing Lyapunov candidate function. Finally, the simulation results verify the effectiveness of proposed control scheme.